Drosophila's contribution to the genetics of learning and memory - Tully, Tim (Henry Stewart Talks, 2008)
Drosophila mutants defective in Pavlovian learning and memory, Training protocols and long-term memory formation, Pavlov's dogs, Biochemical signaling pathways, gene transcription and local control of protein translation, Models of mental retardation, NMDA receptors and the anatomy of long-term memory formation
Reviewed at 2018/05/31